Influence of Family Dialect on English Pronunciation and Intonation: A Study of Language Acquisition Among Chinese EFL Learners - Shuai Hou; Chunwen Yang (Journal of General Education and Humanities, 2025)
This paper investigates the impact of family dialect on the English pronunciation and intonation of Chinese learners by focusing on dialect differences in the process of language acquisition. The method applied was qualitative, involving interviewing ten Chinese translation major university students about their experiences concerning dialect use, parental support, and self-directed learning strategies. Through thematic analysis, four key themes were identified: (1) Dialect Usage and Influence on Pronunciation, where most participants reported phonological transfer effects leading to a “Chinglish” accent; (2) Parental Support, highlighting variations in family involvement in English learning; (3) Learning Strategies, with learners utilizing self-monitoring, media exposure, and shadowing techniques to improve pronunciation; and (4) Challenges and Solutions, where participants expressed difficulties due to a lack of native English-speaking environments but developed compensatory strategies. It supports the theoretical implications of Bronfenbrenner, stressing the role of family in linguistic development. Recommendations are made for dialect-sensitive teaching strategies using emerging education technologies to assist learners, educators, and families in improving English pronunciation and intonation acquisition.